Pedagogical Design of Digital Educational Games for Improving Students’ Mathematical Concepts Understanding: A Systematic Literature Review - Ni Ketut Arum; I Gede Suweken; I Made Ardana (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
The use of digital educational games has become a significant trend in 21st-century learning. Integrating technology into instructional activities offers a promising approach to mathematics education, particularly in enhancing students’ understanding of mathematical concepts. This study aims to analyze how the development of digital educational games can improve students’ conceptual understanding in research conducted between 2015 and 2025. Employing a Systematic Literature Review (SLR) with the PRISMA model, this study utilized the Publish or Perish 8 application to retrieve relevant articles from Scopus and Google Scholar. An analysis of 14 selected studies indicates that the development of digital educational games has a positive impact on students’ understanding of mathematical concepts. However, supporting factors such as game pedagogical design, the validity and practicality of digital educational games as instructional media must be carefully considered. Adhering to sound game-design principles is essential for creating a competitive and enjoyable learning environment that fosters students’ motivation and interest, which in turn enhances their conceptual understanding. Emotional aspects such as feelings of enjoyment, challenge, and pride after completing tasks within the game also show positive correlations with learning outcomes.